Ink under the fingernails : printing politics in nineteenth-century Mexico - Zeltsman, Corinna, 1983- (University of California Press, 2021)
"During the independence era in Mexico, individuals and factions of all stripes embraced the printing press as a key weapon in the broad struggle for political power. Taking readers into the printing shops, government offices, courtrooms, and streets of Mexico City, historian Corinna Zeltsman reconstructs the practical negotiations and discursive contests that surrounded print over a century of political transformation, from the late colonial era to the Mexican Revolution. Centering the diverse communities that worked behind the scenes at urban presses, and examining their social practices and aspirations, Zeltsman explores how printer interactions with state and religious authorities shaped broader debates about press freedom and authorship. Beautifully crafted and ambitious in scope, Ink under the Fingernails sheds new light on Mexico's histories of state formation and political culture, identifying printing shops as unexplored spaces of democratic practice, where the boundaries between manual and intellectual labor blurred"--